Fresh Osteochondral Allograft to Medial Femoral Condyle With Proximal Tibial Opening Wedge Osteotomy - Evan P. Shoemaker BA; Luke V. Tollefson BS; Conner Olson MPH; Nicholas I. Kennedy MD; Robert F. LaPrade MD, PhD (SAGE Publishing, 2024)
Background: Contributors to knee degeneration include mechanical axis malalignment, patellar maltracking, meniscal deficiency, and tibiofemoral instability. Full-thickness osteochondral defects in young, active patients can lead to significant pain and instability. The gold standard treatment for large (>2 cm 2 ) osteochondral defects is an osteochondral allograft (OCA) which addresses the pathologic articular cartilage loss and underlying bone deficiency. While biologic failure of fresh OCAs is reported, the majority of early failures are attributed to unaddressed mechanical malalignment in the coronal plane. Proximal tibial osteotomy (PTO) corrects malalignment thereby unloading the affected medial compartment and the newly placed OCA, improving long-term survivability. Indications: OCAs are indicated for isolated osteochondral defects and lesions in active young patients. PTO is indicated for patients with varus malalignment who risk potential graft failure of the affected medial compartment. Technique Description: The articular cartilage defect is identified, and a guide pin is drilled in the center. The defect is templated and scored around the margins. A reamer is used to drill to a total depth of 7 to 8 mm. The recipient site is then dilated for graft insertion. On the donor graft, the harvest site is outlined and drilled to the proper diameter. Careful measurement is utilized to ensure graft depth measurements match the recipient site. Once sized, the graft is tapped into place obtaining an anatomic fit along its entire periphery. The osteotomy is performed by using guide pins to delineate the plane cutting the tibia. Fluoroscopy confirmed the osteotomy site and angle. A spacing plate was securely inserted with screws, with placement confirmed by fluoroscopy. Results: Fresh OCAs can restore osteochondral defects. PTO corrects malalignment and unloads the affected medial compartment, decreasing the risk of revision graft failure or total knee arthroplasty. Discussion: Clinical and biomechanical studies that compared isolated and concomitant procedures demonstrated that OCA with PTOs had significantly greater survival rates. Significant malalignment increases the risk of graft failure. It remains unclear whether concomitant osteotomy with osteoarticular allografts leads to increased complication risk; inherent risks remain associated with individual procedures. In adolescents, simultaneous corrective osteotomy along with fresh OCA may delay arthroplasty and associated ambulatory restrictions. Patient Consent Disclosure Statement: The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form of approval from the patient(s) with this submission for publication.